Characteristics and Performance of Foreign Direct Investment in Retail Trade: The Case of Japanese Firms - Liang, Jianping; Tang, Jing'an; Liu, Ben (Journal of Comparative International Management)

(untitled) (Management Futures, 2015)
In the international business development, foreign direct investment (FDI) as a general phenomenon has been extensively studied, yet the understanding of particular characteristics of FDI in the retail industry remain limited. The success of international retail trade relies heavily on the understanding of consumers in the host countries. Therefore, this paper analyzed the characteristics and performance of foreign direct investment (FDI) in retail trade using the Japanese FDI data (JFDI) from 1986-2001 as a case. We found (1) an overall trend for JFDI to move from the developed countries to developing countries; (2) a modest correlation between subsidiary size and performance; (3) in certain countries/regions, a positive and significant correlation between entry mode and performance; and (4) a focus of JFDI on the USA and the Greater-China area. The results of this paper provide important implications for countries which want the FDI in retail trade and for companies which want to invest in international retail trade.